A novel formation mechanism of sulfamic acid and its enhancing effect on methanesulfonic acid–methylamine aerosol particle formation in agriculture-developed and coastal industrial areas - H. Wang; S. Wei; J. Yang; Y. Yang; R. Li; R. Wang; C. Zhu; T. Zhang; C. Zhang (Atmospheric Chemistry and Physics)
Sulfamic acid (SFA) significantly impacts atmospheric pollution and poses potential risks to human health. Although traditional sources of SFA and their role in sulfuric acid–dimethylamine new particle formation (NPF) have received increasing attention, the formation mechanism of SFA from HNSO2 hydrolysis with methanesulfonic acid (MSA) and its enhancing effect on MSA-methylamine (MA) NPF have not been studied, which will limit understanding on the source and loss of SFA in agriculture-developed and coastal industrial areas. Here, the gaseous and interfacial formation of SFA from HNSO2 hydrolysis with MSA was investigated using quantum chemical calculations and Born–Oppenheimer molecular dynamics (BOMD) simulations. Furthermore, the role of SFA in the MSA-MA system was assessed using the Atmospheric Cluster Dynamic Code (ACDC) kinetic model. Our simulation results indicate that the gaseous SFA formation from the hydrolysis of HNSO2 with MSA can be competitive with that catalyzed by H2O within an altitude of 5–15 km. At the air–water interface, two types of reactions, the ion-forming mechanism and the proton exchange mechanism to form the SFA− … H3O+ ion pair, were observed on the timescale of picoseconds. Considering the overall environment of sulfuric acid emission reduction, the present findings suggest that SFA may play a significant role in NPF and the growth of aerosol particles, as (i) SFA can directly participate in the formation of MSA-MA-based clusters and enhance the rate of NPF from these clusters by approximately 103 times at 278.15 K and (ii) the SFA− species at the air–water interface can attract gaseous molecules to the aqueous surface and thus promote particle growth.